Regeneration of excised shell by the invasive apple snail Pomacea canaliculata. Issue 1 (2nd January 2017) - Liu, Q.; Zhao, L. L.; Yang, S.; Zhang, J. E.; Zhao, N. Q.; Wu, H.; He, Z.; Yan, T. M.; Guo, J.
Abstract: After excision of shell from Pomacea canaliculata, survival rates, repair process, haemocyte response, and calcium content were observed and quantified for three weeks. The following experimental treatments were used: black-colored individuals with large (BL-group) or small (BS-group) shell heights, yellow-colored individuals with large (YL-group) or small (YS-group) shell heights. The survival rates in BL-, YL-, BS-, and YS-groups after making partial excisions of snail shells were, respectively, 93.59, 94.87, 92.31, and 96.15%. Freshly regenerated shell could be seen at 1 day among the four groups after induction of shell regeneration. Regeneration shell filled the wound after 5–10 days. The area of regenerated shell in yellow-colored individuals was larger than that of black-colored individuals, but the thickness of regenerated shell was not significantly different. Multiple (four times) inductions of shell regeneration significantly enhanced the thickness of newly formed shells. Two types of circulating haemocytes (hyalinocytes and granulocytes) were identified under light microscopy based on Wright's staining. Artificial induction of shell regeneration rendered a significant increase in the number of total circulating haemocytes which was followed by a decrease to pre-wounding levels. This peak value of total circulating haemocytes was 2.86, 2.43, 1.69, and 1.71-fold higher than pre-wounding levels in group BL, YL, BS, and YS, respectively. The number of total circulating haemocytes in yellow-colored individuals was significantly higher than in black-colored. Calcium concentrations in the mantles of snails are favorable for calcium nucleation. It is postulated that calcium content increased in the mantle increase at the start of the experiment and then returned to pre-wounding levels at the end of the experiment. This study shows that apple snails have effective shell regeneration abilities and that haemocytes and calcium transportation appear to play an important role in shell growth and regeneration.